Can Recovery From an Eating Disorder Be Measured? Toward a Standardized Questionnaire - Bachner-Melman, Rachel; Lev-Ari, Lilac; Zohar, Ada H.; Lev, Shay Lee (Frontiers in Psychology, 2018)
Background: There is a clear need for a standardized definition of recovery from eating disorders (EDs) and for self-report instruments to assess where individuals with an ED are situated at a given point of time along their process of illness and recovery. It has been acknowledged that psychological and cognitive symptoms are important to recovery in addition to physical and behavioral indices. This study proposes a 28-item multidimensional questionnaire encompassing the main features of recovery from ED, derived from the endorsement of different criteria by people with a lifetime ED diagnosis, family members and ED clinicians. Methods: Participants were 213 volunteers over the age of 18 (118 people with a lifetime ED diagnosis, 58 healthy family members of people with EDs and 37 ED clinicians), who completed the Eating Disorder-15 and indicated online how important they thought each of 56 criteria were for recovery from an ED. Results Four factors were identified in an exploratory factor analysis: Lack of Symptomatic Behavior (LSB), Acceptance of Self and Body (ASB), Social and Emotional Connection (SEC) and Physical Health (PH). Confirmatory factor analysis using the seven highest loading items from each subscale confirmed the structure validity of a shortened version of this questionnaire, the Eating Disorders Recovery Endorsement Questionnaire (EDREQ), which had excellent goodness-of-fit indices. Despite a few between-group differences, there was general agreement that LSB was most salient to recovery, followed by ASB, SEC and PH in that order. Conclusions Despite the absence of a standardized definition of recovery from ED, there is a general consensus about its components. The EDREQ is a psychometrically sound questionnaire containing items that people with an ED history, their family members and therapists all define as important components of recovery. The inclusion of emotional and psychosocial aspects of recovery in addition to symptomatic and medical aspects is important to expand treatment goals and the concept of recovery from EDs beyond symptom relief and the absence of disease markers. As a clinical tool, the EDREQ stands to assist in setting and refining therapeutic goals throughout therapy, and in establishing standardized, comparable norms for recovery levels in research.